2021
DOI: 10.22270/ujpr.v5i6.507
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Streptococcus Mutans Biofilm Formation and Dental Caries Experience and Antibiotics Resistance in Adult Females

Abstract: Objectives: The aim of this study was to consider the potential association between the formation of salivary streptococcus biofilms and the incidence of caries, as well as with the occurrence of antibiotic resistance among adult mothers in Sana'a, Yemen.  Study design: A total of 261; 25-35 year old females were chosen. Clinical examination of females were performed to estimate dental caries experience with the Silness-Loe index, as well as stimulated saliva were collected to assess biofilm production b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…According to estimates by the World Health Organization (WHO) and United Nations report, deaths due to antimicrobial resistance could increase with the time 4, 5 . Nowadays, antimicrobial resistance (AMR) is a major public health threat, 6,7 and antimicrobial resistance bacteria in different hospital departments are increasing dramatically all over the world and in Yemen this problem is more extensive and complex [8][9][10][11][12][13][14][15][16][17][18][19][20] . As for some details of the previous work in Yemen, these studies mostly focused on studying the sensitivity to antibiotics for each bacteria separately 8-20 , while the current study studied the resistance to all bacterial isolates, and the current study also identified the temporal correlation of the rate of increase in the prevalence of resistance of bacterial isolates to the antibiotics used in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…According to estimates by the World Health Organization (WHO) and United Nations report, deaths due to antimicrobial resistance could increase with the time 4, 5 . Nowadays, antimicrobial resistance (AMR) is a major public health threat, 6,7 and antimicrobial resistance bacteria in different hospital departments are increasing dramatically all over the world and in Yemen this problem is more extensive and complex [8][9][10][11][12][13][14][15][16][17][18][19][20] . As for some details of the previous work in Yemen, these studies mostly focused on studying the sensitivity to antibiotics for each bacteria separately 8-20 , while the current study studied the resistance to all bacterial isolates, and the current study also identified the temporal correlation of the rate of increase in the prevalence of resistance of bacterial isolates to the antibiotics used in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…Denture-associated stomatitis (DAS) is one of the majority common irrefutable symptoms of oral candidiasis 10 , and involves 24-60% of well-worn dentures 11 . Roughly 90% of cases are believed to be caused by yeast 9,12 , typically C. albicans, even though lesions have also been connected with a diversity of further Candida species 10-13 over and above bacteria from numerous genera 3,10,14, 15 . Nowadays, antimicrobial resistance (AMR) is the most important public health threat [16][17][18][19][20] , and AMR bacteria in various hospital departments are increasing exponentially [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, antimicrobial resistance (AMR) is the most important public health threat [16][17][18][19][20] , and AMR bacteria in various hospital departments are increasing exponentially [21][22][23] . According to a published study, 700,000 deaths by reason of antimicrobial resistance are described per annum, and it has been estimated that if proper control and prevention measures are not taken, antimicrobial resistance will turn out to be one of the most important causes of death among nonhospitalized or hospitalized patients all over the world 24 . Oral bacteria such as Staphylococcus aureus, Streptococcus viridians group, and Enterobacteracea are also included as causative agent of systemic infections such as endocarditis, pneumonia, etc., so information on antibiotic profile is of importance in prescribing appropriate treatment in case of infection 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Investigation and survey of dental health problems in Yemen are in spite of everything fairly small and limited, even though there were studies that dealt with the problems of dental caries, the prevalence and pattern of third molar impaction in adults and children, periodontal infections, and causes of extraction of permanent teeth [1][2][3][4][5][6][7][8], however no exploration converge the prevalence of premature loss of primary teeth and its effect on malocclusion. Early loss of primary teeth is a worldwide problem.…”
Section: Introductionmentioning
confidence: 99%